Alleviation of Pain, PAIN Interference, and Oxidative Stress by a Novel Combination of Hemp Oil, Calamari Oil, and Broccoli: A Randomized, Double-Blind, Placebo-Controlled Trial - Carlisle, Carolina; Polley, Kristine; Panda, Chinmayee; Barron, Keri; Hamrock, Meghan; Dominique, Ashley; Metzger, Brandon; Le Brun-Blashka, Sara; Komarnytsky, Slavko (Nutrients, 2023)
Chronic pain is a critical health issue in the US that is routinely managed pharmacologically with diminishing results. The widespread misuse and abuse of prescription opioid pain medications have caused both healthcare providers and patients to seek alternative therapeutic options. Several dietary ingredients have been traditionally used for pain relief and are known to have potential analgesic properties. This double-blind, placebo-controlled randomized clinical trial aimed to test whether a novel combination of full spectrum hemp oil (phytocannabinoids), calamari oil (omega-3 fatty acids), and broccoli (glucosinolates) could reduce chronic pain and attenuate damage from oxidative stress in adults seeking chiropractic care. Participants (average age = 54.8 ± 13.6 years old) were randomly assigned to consume a whole-food, multi-ingredient supplement (n = 12, intervention and standard chiropractic care) or placebo (n = 13, mineral oil and standard chiropractic care) daily for 12 weeks. The subjects’ self-reported perceived pain, pain interference, and reactive oxygen species (ROS) status in the peripheral blood mononuclear cells (PBMC) were quantified at baseline, mid-checkpoint, and postintervention. The intervention was positively associated with a 52% decrease in pain intensity and several parameters of pain interference, including quality of sleep. Decreases in the markers of oxidative stress were also observed in the participants from the intervention group (29.4% decrease in PMBC ROS). Our findings indicated that supplementation with a novel combination of hemp oil, calamari oil, and broccoli has the potential to manage chronic pain when combined with standard chiropractic care, as suggested by its effects on pain intensity and oxidative stress.